Rational development and evaluation of novel formulations for urinary health. (February 2022) - De Seta, Francesco; Johnson, Zoe; Stabile, Guglielmo; Martin, Audrey; Larsen, Bryan
Highlights: DAPAD and citric acid showed antimicrobial activity against UTI-relevant organisms. DAPAD and D-mannose showed expected aggregation of E. coli and some restriction of growth among other uropathogens. Astragalus showed a tendency to reduce IL-6 elaborated by T24 cells. Abstract: Objective: Urinary tract infections (UTI) among women form a substantial part of medical practice and both patients and medical professionals have an interest in non-antibiotic treatments and preventative measures. This research provides preliminary data on a multi-functional composition, DAPAD, which explored several biologic activities of relevance to UTI. Study Design: This formulation included D-mannose, citric acid, three prebiotic compounds, and extracts of dandelion and astragalus. Studies performed employed 4 bacterial strains that have relevance to UTI including E. coli, Proteus mirabilis, Streptococcus agalactiae and Enterococcus faecalis. Results: Key findings from in vitro studies included: DAPAD at full- and half-strength inhibited growth of all UTI bacteria. Evidence for D-mannose agglutination of E. coli was demonstrated. D-mannose also showed unexpected effects on bacterial membrane integrity with vital staining and modest growth restriction. We did not demonstrate growth inhibition by dandelion or astragalus extracts but the latter showed diminished cytokine elaboration by bladder epithelial cells. Conclusion: DAPAD is a multifunctional composition that may warrant further development as a UTI treatment or preventive if supported by clinical evaluation.